Limpeza corporal, ansiedade experimental e privação de sono paradoxal em ratos - Nunes, Helga Caputo [UNESP]; Pezzato, Fernanda Augustini [UNESP]; Hoshino, Katsumasa [UNESP] (My University, 2012)
Objective: Paradoxical sleep deprivation increases grooming behaviors in rats. Discordant data on the change promoted by such deprivation on the experimentally defined anxiety levels have made difficult to assess if the deprivation induced grooming may be used as an experimental model of repetitive behaviors, observed in different psychiatric disorders, due increased anxiety levels. In such context, the present study aims to report data gathering grooming and anxiety in rats. Methods: The degrees of tidiness displayed by female (n=26) and male (n=27) rats were evaluated after a period of maintenance in home-cages provided with wood shavings that have the property to dye animal's fur. In the second study, the tidiness degrees were evaluated after 96 h of sleep deprivation in anxious male rats (n=6) and compared to non-anxious controls (n=6). Results: Females, that are believed to be more anxious than males, displayed higher tidiness (0% colored females x 96% colored males) in the first study. All anxious male rats (100%) that displayed wild running in response to intense acoustic stimulation showed better tidiness than their controls at the end of 96 h sleep deprivation. Conclusions: Our data suggest that self-grooming in rats is tightly related to anxiety and allows the interpretation that its increased occurrence in sleep deprivation results from its anxiolytic or tranquilizing property.
Self-grooming, experimental anxiety and paradoxical sleep deprivation in rats
Keywords: Animal; Anxiety; Compulsive behavior; Grooming; Models; Rats; Sleep deprivation